(3ebGdI aj Cf GdCLQGe GdYdhjI PhGJ GdfaS GdfGWbIs - (3CHh Sdje Hf WGgQ GdSLRj GdSLSJGfjs
(3ChdgG (B:s
(3deG cGf cd LSe WHjYi dg MQcI PGJjI hGYfi Hbhdi WHjYi eG dg SHH ai PGJg jMQcg fMh GdTF GdNGU Hg s
(3BNQgG (B:s
(3aEfg jHjf Pdc ai eYQaI YOO eMQcGJgG GdJi Ydi GdGcQh jQLY ai eYQaI Pdc Edi Yde GdgjFI hjMce YdjgG HMSH eG MceJ Hg GdGQV JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQg eY GdeNWhW Qbe (B301 (3ef faS GdHYKIZes
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(11/253) s
Keywords: (3GdadSaI hGdefWbs